AUDIT TENURE, AUDITOR INDUSTRY SPECIALIZATION AND AUDIT LAG REPORT ON THE FINANCIAL SECTOR ON THE INDONESIA STOCK EXCHANGE 2013-2017 - Ninda Mufidah; Nujmatul Laily (Jurnal Reviu Akuntansi dan Keuangan, 2019)
The purpose of this study is to analyze the effect of audit tenure, audit report lag, and industry auditor specialization on financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017. In addition to this study examining the effect of Audit Tenure (X) on audit report lag (Y), this study also examined auditor industry specialization (Z) influencing the relationship between audit tenure and audit report lag. The population of this study were all financial sector companies listed on Indonesia Stock Exchange (IDX) in 2013-2017. The sampling technique in this study used purposive sampling and the data sources used secondary data with documentation data retrieval techniques. The total number of companies used as research samples is 55 companies. The data analysis technique used in this study is the Moderated Regression Analysis (MRA) with SPSS 25 for Windows. The results of the study show that: (1) audit tenures haven’t a significant effect on audit report lag and (2) auditor industry specialization is not able to weaken the influence of audit tenure on audit report lag.